О глобальной минимизации функций минимума методом минорант - Норкин, В.И.; Онищенко, Б.О. (Теорія оптимальних рішень, 2004)
Stochastic global minimization problems with objective functions in thc form of mathematical expectation of a minimum function are considered. Ways to construct tangent minorants for such functions are specified. A variant of the branch and bound method with minorants estimations of optimum values is described. Results of numerical experiments arc presented.